Connexin43 in Post-Surgical Peritoneal Adhesion Formation - Jia Wang Chua; Moogaambikai Thangaveloo; Debbie Xiu En Lim; Leigh E. Madden; Anthony R. J. Phillips; David L. Becker (Life, 2022)
Objective: Post-surgical peritoneal adhesions are a serious problem for the quality of life and fertility. Yet there are no effective ways of preventing their occurrence. The gap junction protein Cx43 is known to be involved in fibrosis in several different organs and disease conditions often associated with inflammation. Here we examined the Cx43 dynamic expression in an ischemic button model of surgical adhesions. Methods: Using the mouse ischemic button model, Cx43 antisense was delivered in Pluronic gel to attenuate Cx43 expression. The severity of button formation and immunofluorescence analysis of Cx43 and TGF-β1 were performed. The concentration of tissue plasminogen activator via ELISA was also performed. Results: As early as 6 h after button formation, the Cx43 levels were elevated in and around the button and some weak adhesions were formed. By 24 h Cx43 levels had increased further and adhesions were more defined. At 7 days the adhesions were much more robust, opaque, and vascularized, requiring blunt or sharp dissection to break them. Cx43 antisense attenuated its upregulation and, reduced the number and severity of adhesions that formed. Conclusion: Targeting Cx43 after surgical procedures may be a potential therapeutic strategy for preventing adhesion formation or at least reducing their severity.